(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The given article reveals the use of creative arts and body-based practices to develop small motor skills in adolescents with cerebral paralysis. Creative arts and crafts activities such as painting, sculpting and crafts require precision and fine hand movements, promoting improved motor control and coordination. Body-oriented practices such as dance, yoga and special exercises help develop motor skills and strengthen hand muscles. It is important to take an individual approach to each child and work with experienced specialists to develop individual programs and approaches, taking into account their needs and capabilities.